1991
DOI: 10.1063/1.858175
|View full text |Cite
|
Sign up to set email alerts
|

The stability of a sheared density interface

Abstract: This study investigates the stability of stratified shear flows when the density interface is much thinner than, and displaced with respect to, the velocity interface. Theoretical results obtained from the Taylor–Goldstein equation are compared with experiments performed in mixing layer channels. In these experiments a row of spanwise vortex tubes forms at the level of maximum velocity gradient which, because of the profile asymmetry, is displaced from the mean interface level. As the bulk Richardson number is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
126
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(135 citation statements)
references
References 20 publications
9
126
0
Order By: Relevance
“…Browand and Winant [25] first performed shear flow experiments in a stratified environment under conditions for which Holmboe's instabilities are present. Their investigation has been extended further by more recent experiments [11,26,27,28,29,30,31,32].…”
Section: Pacs Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…Browand and Winant [25] first performed shear flow experiments in a stratified environment under conditions for which Holmboe's instabilities are present. Their investigation has been extended further by more recent experiments [11,26,27,28,29,30,31,32].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…It was first identified by Holmboe [10] in a simplified model of a continuous piece-wise linear velocity profile and a step-function density profile. Several authors have expanded Holmboe's theoretical work [11,12,13,14] by considering different stratification and velocity profiles that do not include the simplifying symmetries Holmboe used in his model. Hazel [15] and more recently Smyth and Peltier [16] and Alexakis [17] have shown that Holmboe's results hold for smooth density and velocity profiles as long as the length scale of the density variation is sufficiently smaller than the length scale of the velocity variation.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…If the squared velocity difference exceeds the right-hand side, the surface is unstable and begins to undulate, forming a Kelvin-Helmholtz wave of length L (Figure 1). It has since been appreciated that a variety of hydrodynamic instabilities may develop on a fluid interface within the Richardson number range À3 Ri 1 [Lawrence et al, 1991]. The Richardson number is defined by…”
Section: A Simple Model For Interfacial Instabilitymentioning
confidence: 99%
“…Yet, it is conjectured from numerical simulations 15 that their contribution to diapycnal exchange is approximately equal, as the high mixing efficiency is maintained over a longer period during the slower Holmboe development. The presented observations may be compared with DNS and laboratory studies, [16][17][18] for the specific case when the centres of the shear and density interfaces are vertically displaced with respect to each other. This results in asymmetric Holmboe overturning, or cusping, into the weaker stratified layer.…”
Section: Introductionmentioning
confidence: 99%